(untitled) (Fiep Bulletin - online, 2014)
This study analyzes the theme supervised apprenticeship focusing its relationship with the teachers’ continuous formation and the construction of knowledge of the students trainees in front of the process of appropriation of the concepts of continuous formation, professional development and needs. It is a reflection produced during the course Formation of Teachers: Tendencies of Contemporary Investigations (PIMENTA; FUSARI; ALMEIDA, 2005) supplied in the Program of Masters degree of University of Education, University of São Paulo, that drew contribution to the research "Apprenticeship as thought practice: the production/reconstruction of knowledge for futures teachers" (in development in FEUSP). It uses as methodological procedure the bibliographical research and it especially dialogues with studies in the area of the Didacticism focusing the teachers’ formation. As main considerations, the study stands out as necessary for that the apprenticeship to potentiate the construction of knowledge, not only of the students trainees as well as of the teachers, it to be anchored in a project that promotes the reflection of the educational activity, not only in the individual plan, but in a collective way, being that reflection aided by the theoretical base.